A Severe Case of Murine Typhus Presenting With Anemia and Severe Thrombocytopenia. Issue 3 (April 2018) - Wulff, Jade; Margolin, Judith; Coleman, Nana E.; Demmler-Harrison, Gail; Lam, Fong; Shah, Mona D.
Abstract : We discuss a child with severe thrombocytopenia and mild anemia admitted to the Hematology service who quickly deteriorated to a life-threatening state. However, once rickettsial disease was considered in the differential diagnosis and empiric doxycycline begun, she quickly and fully recovered. A diagnostic panel, including Rickettsia typhi serology, confirmed the diagnosis of murine typhus but this occurred weeks after she had recovered. Given the potential severity of rickettsial diseases and the ease of modern travel across geographic borders, hematology-oncology providers everywhere must consider rickettsial diseases in their differential diagnosis of critically ill children and begin empiric therapy with doxycycline promptly.